2019
DOI: 10.1111/1756-185x.13670
|View full text |Cite
|
Sign up to set email alerts
|

Translation, cross‐cultural adaptation and validation of Nepali version of Health Assessment Questionnaire‐Disability Index in rheumatoid arthritis patients from Nepal

Abstract: Objective To translate, cross‐culturally adapt and validate the Health Assessment Questionnaire‐Disability Index (HAQ‐DI) in Nepali language (Nepali HAQ). Methods Translation was done fulfilling the methodological standards described by Beaton. Comprehensibility testing of the preliminary version was done in 50 rheumatoid arthritis (RA) patients, and a prefinal version was prepared after making changes in the original version to maintain the equivalence with the target version. Psychometric testing was done in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Furthermore, it is used in most clinical trials and observational outcome studies. To date, the HAQ questionnaire is available in English ( 9 ), Dutch ( 10 ), Swedish ( 11 ), Portuguese (Brasil) ( 12 ), French ( 13 ), Spanish (Mexico) ( 14 ), Spanish (Spain) ( 15 ), Italian ( 16 ), German ( 17 ), Arabic (Kuwait) ( 18 ), Korean ( 19 ), Chinese (Singapore) ( 20 ), Danish ( 21 ), Slovak ( 22 ), Indian ( 23 ), Arabic (Egypt) ( 24 ), Spanish (Argentine) ( 25 ), Estonian ( 26 ), Greek ( 27 ), Thai ( 28 ), Turkish ( 29 ), Bengali ( 30 ), Nepali ( 31 ), Malay ( 32 ), Persian ( 33 ), and Japanese ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is used in most clinical trials and observational outcome studies. To date, the HAQ questionnaire is available in English ( 9 ), Dutch ( 10 ), Swedish ( 11 ), Portuguese (Brasil) ( 12 ), French ( 13 ), Spanish (Mexico) ( 14 ), Spanish (Spain) ( 15 ), Italian ( 16 ), German ( 17 ), Arabic (Kuwait) ( 18 ), Korean ( 19 ), Chinese (Singapore) ( 20 ), Danish ( 21 ), Slovak ( 22 ), Indian ( 23 ), Arabic (Egypt) ( 24 ), Spanish (Argentine) ( 25 ), Estonian ( 26 ), Greek ( 27 ), Thai ( 28 ), Turkish ( 29 ), Bengali ( 30 ), Nepali ( 31 ), Malay ( 32 ), Persian ( 33 ), and Japanese ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no studies have yet conducted ICF mapping of patient-reported difficulties to analyze the content validity of ICF core sets in South Asia. This raises the question about the generalizability of ICF Core Sets in non-western developing countries, such as Nepal, where items in physical activity/disability questionnaires frequently must be modified to achieve experiential equivalence [15,16]. Problems with the utility of ICF core sets in a developing country such as Nepal may be indicative of a more widespread problem.…”
Section: Introductionmentioning
confidence: 99%
“…Há também trabalhos de adaptação para outros contextos e idiomas, como o Health Assessment Questionnaire-Disability Index (HAQ-DI) para uso no Nepal (81) , o Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) para uso na Malasia (82) , o Organizational Readiness for Implementing Change (ORIC) para uso na França (83) , o Victorian Institute of Sport Assessment-Achilles Questionnaire (VISA-A) para uso no Chile (84) , entre outros. observações na prática clínica por parte dos profissionais.…”
Section: R26dunclassified